Patterns of Population Displacement in the Former Hot Cloud Area after the 2010 Merapi Volcano Eruption Along the Upper Gendol River Flow - Thomas Dannar Sulistyo; Matteo Wiliam Aryanta; Rilan Tenda Kusuma; Titus Aryo Sasongko (JPG (Jurnal Pendidikan Geografi), 2023)
The Merapi Volcano eruption 2010 caused land damage in several locations, including the District of Cangkringan. After the eruption, residents were relocated to temporary and permanent housing. The site of the 2010 Merapi Volcano eruption's former hot clouds is changing back into a residential area. This study aims to determine the pattern of population displacement after the 2010 Merapi Volcano eruption along the upstream Gendol River. This research uses descriptive and data collection methods of image interpretation, field surveys, and in-depth interviews. Data analysis techniques were conducted using spatial analysis and data triangulation. The pattern of population relocation follows the multiple origin - multiple destination pattern to the temporary shelter and temporary housing, then back to the original residence in the former hot cloud area of the 2010 Merapi Volcano eruption. Relocation back to the former hot cloud area is influenced by (1) being near the land where the informants work, (2) the informants' children use the shelter because they are of marriageable age, (3) taking care of the land that has been inherited or will be inherited, and (4) the bond between the residents around Merapi Volcano and Merapi Volcano itself or the nature around Merapi.